Extraction and GC-MS Analysis of the Volatile Constituents of A Tractylodes macrocephala - Lin, Yin; Wang, Guang-Hua; Yuan, Ke (Asian Journal of Chemistry, 2010)
In present studies A tractylodes macrocephala of three different growing areas of China is the research object. The extraction of volatile constituents from A tractylodes macrocephala of China has been made by steam distillation and solid-phase micro-extraction (SPME). The chemical constituents of volatile oil separated were identified by gas chromatography-mass spectrometry analysis, the relative percentage content of volatile constituents were determined by area normalization method. Gas chromatographic conditions: OV-1701 capillary-tube chromatographic column (30 m × 0.25 mm, 025 μm), temperature-increasing procedure: keep the initial temperature 50 ºC for 2 min and then increase the temperature to 130 ºC at the rate of 10 ºC min-1 and increase the temperature to 190 ºC at the rate of 5 ºC min-1 again and continuous increase the temperature to 240 ºC at the rate of 12 ºC min-1 and keep it for 4 min. The temperature at the sample-feeding entrance is 200 ºC, the temperature at the vaporizing room is 260 ºC, the loaded gas is high-purified (He) and the flowing rate is 0.8 mL min-1, proportion of cleft sample-feeding: 30:1, capacity of sample-feeding: 0.1 mL. Mass-spectrometry conditions: the ion source of electron impact (EI), the ion energy is 70 eV, the temperature of the ion source is 200 ºC, the voltage of the checking device is 350 V, the scanning range is m/z: 33-450 AMU, the scanning speed is 0.5 s, the retrieving data-base is Willey and NIST standard mass-spectrometry data-base. Experimental results show that the type of volatile components is basic similar by steam distillation and SPME method, content of atractylon of A tractylodes macrocephala are high prevalent in three different growing areas. The yield of volatile oil was the highest in Lin'an of Zhejiang province, China, reached 1.92 %, the relative content of atractylon in total volatile oil was the highest, reached 46 %. This experiment result enhances our understanding of volatile constituents in A tractylodes macrocephala and content, the result provides further reference for the development and utilization of A tractylodes macrocephala of China.